Peripheral ossifying fibroma in the lower gingival ridge of an infant. Case report - Serrano - Arrasco, Karen Lizeth (2020)
Peripheral ossifying fibroma (FOP) is a tumor like lesion, exclusively of the gingival tissue. It is considered a hyperplastic gingival growth of reactive type. It is more commonly found in the second decade of life, but very uncommon in infants. When it is found in this group of patients a direct association with a natal or neonatal tooth have been observed. The objective of this report is to present a case of a peripheral ossifying fibroma that occurred in the mandibular alveolar ridge of an infant with a history of a natal tooth extraction at the age of three months.